﻿Coppie in dissolvenza: Don DeLillo e lo spazio psichico del trauma (Altre Modernità, 2011)
This essay discusses the fictional work conceived by Don DeLillo in the aftermath of September 11th. It stresses its intimate dialogue with the coeval visual arts, and in particular with the traumatic nature of performance art. It also insists on the ability of the contemporary historical novel to provide a private and inner background to the most controversial events in American history. In so doing, DeLillo's factual fiction rivals other documentary and reproducible forms of historical representation in its attempt to go beyond the surface of things, and point to a media-conscious future willing to resist the constant states of emergency manufactured in the age of terror.